The Differential Expression of Aqueous Soluble Proteins in Breast Normal and Cancerous Tissues in Relation to Ethnicity of the Patients; Chinese, Malay and Indian. Issue 3 (2nd June 2013) - Liang, Seng; Singh, Manjit; Gam, Lay-Harn
Abstract : Female breast cancer is one of the leading causes of female mortality worldwide. In Malaysia, breast cancer is the most commonly diagnosed cancer in women. Of the women in Malaysia, the Chinese have the highest number of breast cancer cases, followed by the Indian and the Malay. The most common type of breast cancer is infiltrating ductal carcinoma (IDC). A proteomic approach was applied in this study to identify changes in the protein profile of cancerous tissues compared with normal tissues from 18 patients; 8 Chinese, 6 Malay and 4 Indian were analysed. Twenty-four differentially expressed hydrophilic proteins were identified. We evaluated the potential of these proteins as biomarkers for infiltrating ductal carcinoma based on their ethnic-specific expressions. Three of the upregulated proteins, calreticulin, 14-3-3 protein zeta and 14-3-3 protein eta, were found to be expressed at a significantly higher level in the cancerous breast tissues when compared with the normal tissues in cases of infiltrating ductal carcinoma. The upregulation in expression was particularly dominant in the Malay cohort.